2021
DOI: 10.1371/journal.pone.0258642
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 and contributing factors of students’ preventive behavior based on HBM in Gondar, Ethiopia

Abstract: Background The Ethiopian Federal government has locked down schools as one measure to contain Covid-19 pandemic. Psychological effect of COVID-19 on students is increased due to the reopening of schools. The psychological effect of the pandemic is increasing along with physical aspect of health. Therefore, this study aimed to assess the psychological impact of Covid-19 and its contributing factors of students’ behavior in Ethiopia. Methods A cross sectional design was conducted from November to December 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(39 reference statements)
2
4
0
Order By: Relevance
“…Our research findings provide strong evidence that supports the idea suggested in previous studies about the impact of COVID-19 as a phenomenon that has several psychological effects on the population [88,[90][91][92], and our findings add nuance to the prior art by developing this study in the neglected research context of Latin America. Moreover, differently to preceding studies [4,7], the results contribute to a better understanding of this phenomenon among scholars, specifically by refining the dimension "COVID-19 pandemic", with a focus on the items related to the perceptions of individuals regarding their mental health, but avoiding the beliefs of the participants related to the evaluation of strategies to control the health crisis or expectations about potential positive consequences of the vaccination programs in this construct.…”
Section: Implications For Researchsupporting
confidence: 89%
“…Our research findings provide strong evidence that supports the idea suggested in previous studies about the impact of COVID-19 as a phenomenon that has several psychological effects on the population [88,[90][91][92], and our findings add nuance to the prior art by developing this study in the neglected research context of Latin America. Moreover, differently to preceding studies [4,7], the results contribute to a better understanding of this phenomenon among scholars, specifically by refining the dimension "COVID-19 pandemic", with a focus on the items related to the perceptions of individuals regarding their mental health, but avoiding the beliefs of the participants related to the evaluation of strategies to control the health crisis or expectations about potential positive consequences of the vaccination programs in this construct.…”
Section: Implications For Researchsupporting
confidence: 89%
“…Social support was measured using the Oslo Social Support Scale (OSSS-3). It consists of three items, with a total score of 3–14 points, of which 3–8 points are low social support, 9–11 points are moderate, and 12–14 are solid social support [ 34 ]. In the current study, Cronbach’s alpha was 0.85.…”
Section: Methodsmentioning
confidence: 99%
“…However, students who ate three times per day were less likely to have stress (OR = 0.01, 95% = CI = 0.00-0.17, p < 0.001). (Tesema et al, 2021) and stress. The students from the 9th and 12th grades had higher odds to experience these mental disorders than others probably because they were preparing to sit for the national exam, and they were frequently exposed to social media platforms that would spread rumors, fabricated news, and biased information about COVID-19.…”
Section: Risk and Protective Factors Of Depression Symptomsmentioning
confidence: 99%